Initial multicentre experience using the neuroform atlas stent for the treatment of un-ruptured saccular cerebral aneurysms. (3rd May 2020) - Baek, Jin Wook; Jin, Sung-Chul; Kim, Jung Hoon; Yoo, Min Wook; Jeong, Hae Woong; Seo, Jung Hwa; Han, Ji Yeon; Heo, Young Jin; Kim, Sung Tae
Abstract: Purpose: The Neuroform Atlas is a self-expandable and low-profiled stent that is used for aneurysm neck scaffolding and has been recently approved for clinical practice in Korea. We present our initial experiences of endovascular coiling using the Neuroform Atlas stent. Materials and methods: All cerebral aneurysms treated by stent-assisted coiling with a Neuroform atlas stent in two institutions between February and May 2018 were retrospectively evaluated. Fifty-one patients with 55 un-ruptured saccular cerebral aneurysms (mean size: 4.72 ± 1.81 mm, mean neck diameter: 3.82 ± 1.23 mm, mean dome-to-neck ratio: 1.21) were included in our study (40 females, mean age: 59.29 ± 11.96 years). Patient demographics, aneurysm characteristics, initial angiographic post procedural outcomes, and clinical and angiographic follow-up data were analysed. Results: There was one case of procedural failure due to a downward slip during stent deployment. The technical success rate was 98.2% (54/55). A post-procedure control angiogram showed complete occlusion in 27 (50%), residual neck in 16 (29.6%) and residual sac in 11 (20.4%) aneurysms. There were no procedure-related complications. In one case, a symptomatic thromboembolism with left hand grip weakness (grade IV) was observed two days after the procedure and resolved at discharge. The modified Rankin scale score at discharge was 0 in all patients. Angiographic follow-up data at a mean of 4.8 months were available for 51/54 (94.4%) aneurysms. Among them, 27 aneurysms (52.9%) were stable, 20 aneurysms (39.2%) showed progressive occlusion and 4 aneurysms showed an increased modified Raymond Roy occlusion classification score (only one of these patients was included in the recanalization criteria). Conclusion: Our findings suggest the Neuroform Atlas stent can be useful for the coiling of cerebral aneurysms without significant complications regardless of aneurysm location.